The impact of changes in common property resource management on intrahousehold allocation - Maggs, Philip; Hoddinott, John F. (International Food Policy Research Institute, 1997)
In developing countries, common property resources (CPRs) can be an important source of income for certain individuals within households. This paper demonstrates that if a change in the management of CPRs imposes costs on these individuals, or causes a decline in the prices or productivities associated with goods produced from the CPRs, the intrahousehold allocation of resources may alter in a manner detrimental to those individuals. The paper also shows that the assumption of a unitary household model causes the detrimental effects of certain CPR policy interventions to be overlooked.